Usia Menarche dan Pola Menstruasi Berdasarkan Status Gizi Remaja Putri - Setyaningsih, Wahyu (Malang Journal of Midwifery (MAJORY); Vol 1 No 1 (2019): MAJORYDO - 10.31290/majory.v1i1.2192, 2021)
Adolescent nutrition problems need to be the focus of attention because the nutritional status of young women (premarital) has a large influence on the health of pregnancy and birth if the teenager becomes a mother. This study was conducted to analyze the age of menarche and menstrual patterns based on the nutritional status of young women in Malang City. This study was a cross-sectional study carried out in Senior High School 3 Malang, with the subject of 75 young women selected by simple random sampling method. Data on the characteristics, age of menarche and menstrual patterns were obtained using a questionnaire with structured interviews. Data about weight, height, upper arm circumference and abdominal circumference were obtained by measurement. Data analysis was done by univariate and bivariate (chi-square). The results showed that 14.67% of female adolescents were included in malnutrition status, 13.33% over nutrition status (BMI / U), 25.33% had SEZ, and 22.67% more nutritional status (abdominal circumference> 80cm). This study showed no significant relationship between age of menarche with nutritional status (p> 0.05), but there was a significant relationship between menstrual patterns and nutritional status (p <0.05). Efforts to improve nutritional status for quality must begin as early as possible, especially for school children as the next generation of the nation. Keywords: age of menarche, menstrual patterns, nutrition status